Cancer management : a multidisciplinary approach : medical, surgical, & radiation oncology - Pazdur, Richard; Coia, Lawrence R; Hoskins, William J; Wagman, Lawrence D (Oncology Group, 2003)
The handbook focuses on various treatments of cancer within a multidisciplinary approach. Intended for professional public.
Keywords: Neoplasms; Disease Management; nádory; mezioborová komunikace; Radiation Oncology; Interdisciplinary Communication; radiační onkologie; chirurgická onkologie; Surgical Oncology; radioterapie; Radiotherapy; farmakoterapie; Drug Therapy; management nemoci; onkologie